The Positivism Paradigm in Internal Audit Research: A Perspective of Contemporary Accounting Research - Cahyono, Suham; Daniel, Debby Ratna (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2023)
ABSTRACTThis study aims to investigate the dominance of research with the paradigm of positivism in accounting, especially research related to the internal function of audit. The dominant paradigm in accounting research to date is the positivist paradigm. In internal audit, all things are not only seen from the facts that are on the surface and concluded directly from the existing data, but also must understand the meaning contained on it. Therefore, it is necessary to have another paradigm that contradicts positivism and covers its limitations. Anti-positivist paradigms, that are interpretivism, radical humanist, radical structuralist, critical, and postmodernist paradigm, should be widely used in internal audit research. The anti-positivism paradigm raises the heterogeneity of the mainstream paradigm which has a positive impact on the development of internal audit research.Keyword: Paradigma Positivism, Internal Audit, Qualitative Research Method